2019
DOI: 10.1155/2019/6806540
|View full text |Cite
|
Sign up to set email alerts
|

Intradiscal Injection of Induced Pluripotent Stem Cell-Derived Nucleus Pulposus-Like Cell-Seeded Polymeric Microspheres Promotes Rat Disc Regeneration

Abstract: Background. Cell replacement therapy is an attractive alternative for treating degenerated intervertebral discs (IVDs), which are related to the reduction of nucleus pulposus-like cells (NP-lCs) and the loss of the extracellular matrix. Induced pluripotent stem cells (iPSCs) which resemble embryonic stem cells are considered to be a potential resource for restoring NP-lCs and disc homeostasis. Here, we proposed an efficient two-step differentiation protocol of human iPSCs into NP-lCs and continuously tested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 41 publications
0
53
0
Order By: Relevance
“…In the rabbit model, the operated spine (L2/3–L4/5) was surgically harvested, and soft tissue and vertebral bone were removed from the IVDs under sterile conditions. The harvested IVDs (rat, rabbit) were fixed with 4% (w/v) paraformaldehyde for 48 h at room temperature and embedded in paraffin 21 , 22 , 31 . Transverse sections (5 μm thick) of the middle portion of the IVD were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…In the rabbit model, the operated spine (L2/3–L4/5) was surgically harvested, and soft tissue and vertebral bone were removed from the IVDs under sterile conditions. The harvested IVDs (rat, rabbit) were fixed with 4% (w/v) paraformaldehyde for 48 h at room temperature and embedded in paraffin 21 , 22 , 31 . Transverse sections (5 μm thick) of the middle portion of the IVD were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Since then, a wide variety of studies have reported the derivation of specific cell types from iPSCs, generating robust and reproducible phenotypes in vitro that reflect diseases intrinsic to the cellular level [ 35 ]. Specifically, evidence that reprogrammed cells can be differentiated into osteoblasts [ 54 , 55 , 56 ], chondrocytes [ 57 , 58 , 59 , 60 ], myoblasts [ 61 ], nucleus pulposus cells [ 47 , 48 , 49 ] and tenocytes [ 62 ] has recently impacted musculoskeletal research and changed orthopedic medicine. Nevertheless, the use of iPSCs for studying the wide variety of musculoskeletal conditions has been explored to a limited extent ( Table 1 ) in comparison with conditions affecting nervous or cardiac pathologies, even when investigating genetic disorders where symptoms affect several organs or systems [ 63 , 64 , 65 , 66 ].…”
Section: Disease Modelingmentioning
confidence: 99%
“…In the case of degenerative disc disease, several studies have focused on the resettlement of cells that had been lost in the intervertebral disc by injecting iPSCs [ 146 ] differentiated into nucleus pulposus [ 48 ] or notochordal cells [ 147 ], with very promising outcomes. These studies used different hydrogels with and without growth factors.…”
Section: Ipscs In Regenerative Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials in humans have revealed significant pain relief and improvement of the quality of life of patients, albeit with very few signs of IVD regeneration [14]. Thus, a number of studies have suggested therapeutic in vitro manipulation of MSCs prior to their injection, in order to generate NP-like cells, using growth factor-driven differentiation protocols [15,16]. Co-culture experiments have also been performed to evaluate the effects of injected MSCs on resident NP cells [17,18].…”
Section: Introductionmentioning
confidence: 99%